Derivation and Characterization of Isogenic OPA1 Mutant and Control Human Pluripotent Stem Cell Lines - Katherine A. Pohl; Xiangmei Zhang; Johnny Jeonghyun Ji; Linsey Stiles; Alfredo A. Sadun; Xian-Jie Yang (Cells)
Dominant optic atrophy (DOA) is the most commonly inherited optic neuropathy. The majority of DOA is caused by mutations in the OPA1 gene, which encodes a dynamin-related GTPase located to the mitochondrion. OPA1 has been shown to regulate mitochondrial dynamics and promote fusion. Within the mitochondrion, proteolytically processed OPA1 proteins form complexes to maintain membrane integrity and the respiratory chain complexity. Although OPA1 is broadly expressed, human OPA1 mutations predominantly affect retinal ganglion cells (RGCs) that are responsible for transmitting visual information from the retina to the brain. Due to the scarcity of human RGCs, DOA has not been studied in depth using the disease affected neurons. To enable studies of DOA using stem-cell-derived human RGCs, we performed CRISPR-Cas9 gene editing to generate OPA1 mutant pluripotent stem cell (PSC) lines with corresponding isogenic controls. CRISPR-Cas9 gene editing yielded both OPA1 homozygous and heterozygous mutant ESC lines from a parental control ESC line. In addition, CRISPR-mediated homology-directed repair (HDR) successfully corrected the OPA1 mutation in a DOA patient’s iPSCs. In comparison to the isogenic controls, the heterozygous mutant PSCs expressed the same OPA1 protein isoforms but at reduced levels; whereas the homozygous mutant PSCs showed a loss of OPA1 protein and altered mitochondrial morphology. Furthermore, OPA1 mutant PSCs exhibited reduced rates of oxygen consumption and ATP production associated with mitochondria. These isogenic PSC lines will be valuable tools for establishing OPA1-DOA disease models in vitro and developing treatments for mitochondrial deficiency associated neurodegeneration.